Volatility Modelling and Forecasting of Indonesia-USA Currency Using Constant Conditional Multivariate GARCH - Juwita Suwondo (Indonesian Journal Publisher, 2025)
This paper estimated and forecasted the volatility of USD/IDR exchange rate using Constant Conditional Multivariate GARCH (Generalized Autoregressive Conditional Heteroskedasticity) and ARIMA (Autoregressive Moving Average) as the methods. The objective of this study is to comprehend and to execute a projection of the currency of Indonesia and Philippines while understanding the rapid movement of the variables (volatilility). The variables used are USD/IDR, Jakarta Stock Exchange Composite Index (JCI), World Oil Price, and Nominal Broad U.S. Dollar Index. The data was daily, taken from World Bank, Federal Reserve Economic Data, and Indonesian Stock Exchange during 2006-2025. The result showed that there was short term autoregressive moving average dynamics in USD/IDR return, through Mean Equation. The GARCH model showed high persistence of volatility and the shocks showed indication of long-lasting in term of duration. Persistent volatility implied that USD/IDR was sensitive to external shocks. The result also confirmed that the volatility is time-varying, meaning the fluctuations tend to cluster into specific downturn or upturn movement. The method used in this study did not consider about different period in volatility (leverage effect) as it used symmetric volatility as assumption.